Penelitian Etnografi : Dampak Sosial para Pekerja Shift di Network Operation Center (NOC) - Hutabarat, Berman J; Sayuti, Sayuti; Heikal, Jerry (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study explores the social challenges experienced by shift workers in a telecommunication company, particularly those working at the Network Operation Center (NOC) of PT Link Net. Shift work is essential for maintaining uninterrupted network operations; however, it often disrupts workers’ ability to balance professional responsibilities with family and social life. The research aims to examine how shift schedules affect interactions with nuclear families, extended families, and community or hobby groups, as well as how workers adapt to these conditions. Using an ethnographic approach, data were collected through in-depth interviews and participant observation with five shift workers who met the study criteria. Thematic analysis revealed three main shared challenges: difficulty synchronizing schedules with family and friends, feelings of isolation due to limited opportunities for direct social interaction, and the need to allocate specific time to stay connected through digital platforms. These findings highlight how workers redefine “quality time,” shifting its meaning from duration to the depth of interaction. The study suggests that workplace policies should consider more flexible arrangements to support work-life balance and reduce the negative social impacts of shift work.